The basicity makes the difference: improved canavanine-derived inhibitors of the proprotein convertase furin - Van Lam van, Thuy; Heindl, Miriam Ruth; Schlutt, Christine; Böttcher-Friebertshäuser, Eva; Bartenschlager, Ralf; Klebe, Gerhard; Brandstetter, Hans; Dahms, Sven O.; Steinmetzer, Torsten (ACS medicinal chemistry letters, 2021)
Furin activates numerous viral glycoproteins, and its inhibition prevents virus replication and spread. Through the replacement of arginine by the less basic canavanine, new inhibitors targeting furin in the trans-Golgi network were developed. These inhibitors exert potent antiviral activity in cell culture with much lower toxicity than arginine-derived analogues, most likely due to their reduced protonation in the blood circulation. Thus, despite its important physiological functions, furin might be a suitable antiviral drug target.